Older Adults’ Lifelong Learning in Indonesia: Motivational Ecosystem, Institutional Design, and Family Capital - Sulistiono, Eko; Novansyah, Imbar; Saepudin, Asep; Yasepta, Rengky (Journal of Nonformal Education, 2026)
Background- This study addresses the growing demand for effective educational approaches for older adults in the context of global population aging, particularly within community-based programs in Indonesia. Research Urgency- Despite increasing elderly participation in learning programs, the underlying motivational mechanisms that sustain their engagement remain insufficiently explored, especially in non-formal and culturally embedded settings. Research Objectives- The study aims to investigate the key factors that motivate elderly learners to participate in and sustain engagement in a 40-day residential community education program at Pesantren Daarut Tauhiid, Bandung. Research Method- A qualitative case study design was employed involving nine participants, including elderly learners, a program coordinator, and family members. Data were collected through semi-structured interviews, non-participant observation, and document analysis, and analyzed using the Miles–Huberman–Saldaña interactive model. Research Findings- The findings identify a three-pillar motivational ecosystem consisting of internal motivation, program-level support, and family support. Internal motivation is shaped by life experience, spiritual beliefs, existential awareness, and goal orientation. Program support includes social and instructional elements that facilitate participation, while family support provides emotional, informational, and practical assistance. Research Conclusion- The interaction of these three dimensions plays a crucial role in sustaining elderly learning engagement in community-based programs. Research Novelty/Contribution- This study offers an integrated motivational ecosystem model that combines internal, institutional, and familial factors, contributing to the advancement of geragogical theory and providing practical guidance for designing effective elderly education programs.